Design and Evaluation of Isolated Herbal Extracts of Aloin, Proanthocyanidin, Quercetin Loaded Microsponge as Sunscreen Gel - Muruganantham, Venkatrajan; Venkateswarlu, Bendi Sri; Chinraj, Vignesh (Asian Journal of Biological and Life Sciences)
The goal of this research is to produce and create a technique for using microsponge gel as a polyherbal formulation, as well as methods for evaluating sunscreen qualities. Using the quasiemulsion solvent diffusion method, polyherbal extracts as an active component for preparing microsponge formulations with changes in the ratio of a drug, i.e. Polyherbal extracts, ethylcellulose as a polymer, and Polyvinyl alcohol as an emulsifier present in the formulation, was successfully obtained. The significant characterisation was considered for the formulations developed. The physical description of a microsponge formulation with a Gel-3 covering shows that it has a higher loading efficiency and yield. The microsponge formulation was made with the assistance of a gel and carbopol, and then pH, viscosity, spreadability, drug content, and in-vitro release tests were done. The majority of microsponge preparations are made by putting drugs into them, and the results are easy to replicate. Using a Franz diffusion cell, the optimal formulation of microspongeloaded gel of polyherbal extract. The microsponge-loaded sunscreen gel has an outstanding release rate, according to the release profile.
Keywords: Aloin; Microsponge; Polyherbal microsponge gel; Proanthocyanidin; Quasi-emulsion solvent diffusion method; Quercetin; Sunscreen